Late-onset sepsis: Epidemiology, evaluation, and outcome - Bentlin, Maria Regina [UNESP]; Rugolo, Ligia Maria Suppo de Souza [UNESP] (American Academy of Pediatrics (AAP), 2010)
Late-onset neonatal sepsis is a common serious problem in preterm infants in neonatal intensive care units. Diagnosis can be difficult because clinical manifestations are not specific and none of the available laboratory tests can be considered an ideal marker. For this reason, a combination of markers has been proposed. Complete blood count and acute-phase reactants evaluated together help in diagnosis. C-reactive protein is a specific but late marker, and procalcitonin has proven accurate, although it is little studied in newborns. Blood, cerebrospinal fluid, and urine cultures always should be obtained when late-onset sepsis is suspected. Blood culture, the gold standard in diagnosis, is highly sensitive but needs up to 48 hours to detect microbial growth. Various cytokines have been investigated as early markers of infection, but results are not uniform. Other diagnostic tests that offer promise include: neutrophil surface markers, granulocyte colony-stimulating factor, toll-like receptors, and nuclear factor kappa B. The greatest hope for quick and accurate diagnosis lies in molecular biology, using real time polymerase chain reaction combined withDNAmicroarray. Sepsis and meningitis may affect both the short- and long-term prognosis for newborns. Mortality in neonatal meningitis has been reduced in recent years, but short-term complications and later neurocognitive sequelae remain. Late-onset sepsis significantly increases preterm infant mortality and the risk of cerebral lesions and neurosensory sequelae, including developmental difficulties and cerebral palsy. Early diagnosis of late-onset sepsis contributes to improved neonatal prognosis, but the outcome remains far from satisfactory. © 2010 by the American Academy of Pediatrics.